Montmorillonite separated from bentonite - its modification and possibility to use in anionic polymerization of e-caprolactam for preparation of nanocomposites - Kelar, K.; Jurkowski, B.; Mencel, K. (Polimery, 2022)
Montmorillonite fraction (Table 1) was separated from bentonite using filtration and sedimentation methods (Fig. 1 and 2). Natural Na-montmorillonite (MMT) is hydrophilic and incompatible with most of polymers. To prepare organophilic MMT, sodium cation present in interlayer galleries has been exchanged with organic octadecylammonium cation. This exchange, leading to preparation of modified MMT (ZMMT) characterized with higher content of organic parts, was confirmed using FTIR method (Fig. 3 and 5). The results of laser analyses of particle dimensions’ distributions of MMT separated from bentonite and commercial one (Fig. 4). Differential thermal analysis was used to determine the values describing the course of e-caprolactam anionic polymerization in the presence of ZMMT or commercial MMT or without them (Table 2). None of significant differences was found.